A rare presentation of caesarean scar pregnancy: a case report - Manku, Harpoonam; Nivetha, B.; Jyothi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Caesarean scar pregnancy (CSP) or retained products of conception is a rare but life-threatening complication. It is an abnormal implantation of the gestational sac or retained products of conception into the myometrium and a fibrous scar after a previous caesarean section. The incidence of such cases is on the rise due to the increase in caesarean sections worldwide. A 37-year-old P2L2A1 (two previous caesarean sections and one spontaneous abortion followed by dilation and curettage) presented with complaints of vaginal bleeding and lower abdominal pain. She was diagnosed as a case of CSP with retained products of conception by ultrasonography and confirmation of the diagnosis was done by magnetic resonance imaging. An exploratory laparotomy was performed and the patient was successfully managed. Treatment must be individualized depending on the patient’s hemodynamic profile, size, extent, depth, and vascularity, caesarean pregnancy, future fertility wishes, and compliance for follow-up.